"... i korabl plybyet" - Gaverdovsky, Y. K. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to trace the most noteworthy landmarks of the gymnastic technique development. The author analyses and classifies the various periods of the gymnastic technique's development in all events of the gymnastic competition at the period from the middle of this century up to the present. He concludes that the gymnastics must change itself in the direction of exercises' complication in elements and their combinations. This problem can be solved with a help of disigning the more "elastic" and "active" apparatus. It is necessary to realize the total system of safety (the soft and controled apparatus, the change of the accurate landing conception), to develope the disigning in the field of combinations, to emphasize the artistic aspect of gymnastics, to limit the role of the all-round competition.